A SURVEY OF PROBLEMS IN WRITING EXPERIENCED BY THE THIRD YEAR STUDENTS OF ENGLISH STUDY PROGRAM FKIP UNIVERSITAS RIAU - Samuel Dimatteo Tobing; Fadly Azhar; Eliwarti Eliwarti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This reserach aimed at finding out the most common problems in writing experienced by the third year students of English Study Program FKIP Universitas Riau. This research is a descriptive quantitative with survey and the population of the survey is 110 third year students of English Study Program FKIP Universitas Riau. A questionnaire was used to collect the data to find out most common problems in writing of the students. The questionnaire contained 21 statements and divided into 2 groups: internal problems (Organization, Spelling, Grammar and Capitalization) and external problems (Learners’motivation, teachers feedback and inadequate time) with 9 items. The questionnaire was accessed online via google forms. Every statement in questionnaire used 5 point Likert-Scale start from strongly agree to strongly disagree. The result showed the most problem in writing experienced in internal problem is spelling problem with 229.3 average points. The other problems are: organization problem with 217.3 average points, grammar problem with 213.6 average points and the last is capitalization 195 average points . The most problems in external problem is inadequate time with 246 average points. The other problems learners’ motivation with 243.3 average points and teachers’ feedback with 218 average points.Key Words: Survey, Writing, Writing problems.